RADIOTHERAPY IN MANAGEMENT OF BRCA-POSITIVE OVARIAN CANCER - T. V. Gorodnova (Sibirskij Onkologičeskij Žurnal, 2017)
Cancer cells with the loss of BRCA 1 or BRCA 2 function are unable to repair DNA double-strand breaks and demonstrate the increased sensitivity to various DNA-damaging agents. We aimed to describe successful treatment outcomes in two patients with BRCA1-associated ovarian cancer, who showed a complete clinical response to radiotherapy in combination with platinum-based chemotherapy. The progression-free survival was 11 months in one case and 8 months in another case.